Fabrication and performance of shape‐stable phase change materials based on epoxy group crosslinking. Issue 28 (13th March 2021) - Tao, Lijuan; Chen, Sai; Liu, Haihui; Han, Na; Li, Wei; Zhang, Xingxiang
Abstract: Shape‐stable phase change materials (SSPCMs) have attracted increased attention as they can be used in applications such as solar energy storage materials and smart textiles. Hexadecyl acrylate (HDA) was free‐radical copolymerized with allyl glycidyl ether (AGE) to form a copolymer with epoxy groups. It was further solidified with diethylenetriamine to form a series of novel SSPCMs. HDA could be limited to a stable 3D cross‐linking network constructed from epoxy groups, giving PCM excellent shape stability. Infrared spectroscopy and hydrogen nuclear magnetic spectroscopy showed the successful fabrication of poly(hexadecyl acrylate) (PHDA) with epoxy group. The maximum enthalpies of the SSPCMs with 5 wt% AGE during heating and cooling were 86 and 86 J/g, respectively, which indicated that they have good thermal energy storage densities. The initial melting and freezing temperatures were 32 and 29°C, respectively, which were within the comfortable temperature range of human body. In addition, the thermal decomposition temperature of SSPCMs was higher than 270°C. After 50 thermal cycles, the materials still showed excellent phase change performances. Moreover, the specimen with low degree of cross‐linking had similar temperature control and thermal response capabilities to PHDA. These SSPCMs exhibited excellent thermal performance, thermal reliabilities, and stabilities. Therefore, they were expected to be applied in various applications, including solar energy storage, energy‐saving buildings, and wearable temperature control textiles. Abstract :